Reconstructing Security after Conflict - Jackson, P. author. aut Link
XIII, 236 p.
Keywords: A long-term evaluation and analysis of the UK's involvement in Sierra Leone before and after the conflict which ended in 2002. This book looks at how UK intervention moved from initial involvement through to war fighting and then post-conflict reconstruction, specifically of the security infrastructure.